MAPPING TRENDS AND RESEARCH TOPICS ON BIBLIOMETRIC PUBLIC OPEN SPACES FROM 2021-2025 - MULADI, AGUM (Noble Cendekia Indonesia, 2025)
This bibliometric research focuses on mapping research using the database of research articles from the ScienceDirect website. This research was conducted to understand the development of research in the field of environment, particularly on the topic of public open spaces. Data collection was conducted based on the Science Direct database with the keyword bibliometric public open spaces, the publication category being research articles, totaling 647 articles published in the years 2021-2025. Data analysis and visualization were conducted using VOSViewer. The analysis results show that the dominant research topics in bibliometric public open spaces include publication and innovation. Articles on the topic of bibliometric public open spaces found on the ScienceDirect website have research potential and opportunities divided into 7 clusters with 268 items, covering discussions on concepts, models, thoughts, approaches, effectiveness, and efficiency of articles relevant to the topic of bibliometric public open spaces over a period of 5 years. This research is still limited by utilizing the Science Direct website database with several constraints used to filter the data to be collected, then in the extraction of metadata, VOSViewer is used to create visualizations of mapping and topic clustering. Furthermore, this research can serve as a reference and inspiration for other researchers who will study the topic of bibliometric public open spaces.